2007
DOI: 10.1158/1078-0432.ccr-06-2294
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Is a Relevant Therapeutic Target in Acute and Chronic Lymphoid Malignancies: Down-Regulation Enhances Rituximab-Mediated Apoptosis and Complement-Dependent Cytotoxicity

Abstract: Purpose: The antiapoptotic Bcl-2 family member protein Mcl-1is dynamically regulated in transformed B-cells, has a short mRNA and protein half-life, and is rapidly processed during apoptosis. Multiple therapies cause down-regulation of Mcl-1in chronic and acute lymphoid leukemia (CLL and ALL) cells. Mcl-1 has also been reported to mediate resistance to rituximab in CLL. We therefore investigated whether direct reduction of Mcl-1 was sufficient to induce apoptosis and increase sensitivity to rituximab. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 40 publications
8
102
0
1
Order By: Relevance
“…Of note, we found that the inhibition of Mcl-1 using siRNA also resulted in significant apoptosis in the absence of etoposide, which is in contrast to the finding of others on solid tumors (Thallinger et al, 2003, Thallinger et al, 2004. However, this observation is similar to that found on other studies on hematological malignancies (Hussain et al, 2007;Quinn et al, 2011), illustrating the important biological role of Mcl-1 in leukemic cells. In addition, siMcl-1, in combination with etoposide dramatically enhanced apoptosis compared with siRNA alone or etoposide alone.…”
Section: Discussionsupporting
confidence: 85%
“…Of note, we found that the inhibition of Mcl-1 using siRNA also resulted in significant apoptosis in the absence of etoposide, which is in contrast to the finding of others on solid tumors (Thallinger et al, 2003, Thallinger et al, 2004. However, this observation is similar to that found on other studies on hematological malignancies (Hussain et al, 2007;Quinn et al, 2011), illustrating the important biological role of Mcl-1 in leukemic cells. In addition, siMcl-1, in combination with etoposide dramatically enhanced apoptosis compared with siRNA alone or etoposide alone.…”
Section: Discussionsupporting
confidence: 85%
“…We recently showed, using Mcl-1-specific small interfering RNA, that Mcl-1 down-regulation alone is sufficient to promote mitochondrial membrane depolarization and apoptosis in CLL cells. 5 This Mcl-1 reduction also enhances CLL cell sensitivity to rituximab-mediated direct and complement-dependent cytotoxicity, but not antibodydependent cellular cytotoxicity. 5 Agents that target Mcl-1 protein expression in CLL cells, such as flavopiridol 19,20 and the novel agent silvestrol, 21 may therefore be of significant benefit in combination chemoimmunotherapy.…”
Section: Resultsmentioning
confidence: 93%
“…Mcl-1 modulation impacts response of CLL cells to various commonly used therapeutic agents, and loss of Mcl-1 is by itself sufficient to induce apoptosis in CLL cells. [5][6][7] Recent reports have also revealed a correlation between lower Mcl-1 protein 8 and mRNA levels 9 with known biologic prognostic markers and improved outcomes in patients with CLL.…”
Section: Introductionmentioning
confidence: 98%
“…42 Here, we provide evidence that MCL1 may be a redox-sensitive protein and its glutathionylation status could affect its stability. Because MCL1 has a critical role in prolonging the CLL cell survival, especially in a tumor-stroma context, 43,44 and is strongly associated with resistance to fludarabine, 28,29 rituximab, 45 chlorambucil, and prednisone, 46 the thiol-mediated abrogation of MCL1 by PEITC suggests a novel mechanism that may be exploited to overcome drug resistance by combining PEITC with these anti-CLL agents.…”
Section: Discussionmentioning
confidence: 99%